A new artificial bee colony based on neighbourhood selection. (28th June 2019) - Xiong, Xiaoyan; Tang, Jun
In this paper, we present a new artificial bee colony (ABC) for solving numerical optimisation problems. In the original ABC, a new candidate solution is generated based on the current solution and a randomly selected one. However, the random selection method is unstable. To accelerate the search, a new neighbourhood selection is proposed. For each current solution, we firstly randomly select some solutions from the current population. Then, we choose the best one among those solutions as the neighbourhood solution to generate new solutions. To verify the performance, we test several classical numerical optimisation problems. Simulation results show that our approach outperforms the original ABC and some improved ABC versions.